Assessment of contamination levels in methamphetamine-tested properties in New Zealand. (November 2019) - Russell, M.; Ivory, Bradley; McKinnel, Megan
Highlights: Test result data from >1000 methamphetamine-contaminated properties was collected. 75% of wipes were "positive", with an average of 2.73 μg/100 cm 2 . The "average highest" result (within a property) was 8.14 μg/100 cm 2 . Less than 1% of results were >30 μg/100 cm 2 . Abstract: In November 2016, whilst in draft, the New Zealand Standard (NZS8510:2017) for the "Testing and Decontamination of Methamphetamine-Contaminated Properties" considered two acceptable post-decontamination re-occupancy methamphetamine levels; 1.5 μg/100 cm 2 if the contamination was caused by smoking methamphetamine and 0.5 μg/100 cm 2 if the contamination was caused by the manufacture of methamphetamine. In response to this, research carried out at this laboratory included the analysis of data obtained from over a thousand pre-decontamination property test reports with the aim of understanding the variation in the levels of contamination, that could be expected, among the wider New Zealand (contaminated) housing stock. The vast majority of the reports originated from public sector agency properties where methamphetamine was suspected to have been used. Although it could not be ruled-out, none of the properties had been associated with any suspicion of drug production. Thus, a further intention of the study was to assess and portray the levels of contamination that would be expected to be produced through methamphetamine use, commonly smoking. As such, it is expected that the data might be useful from an environmental exposure perspective and inform further research in this area. The assessment also discusses its potential as evidence in criminal cases where there may be discrepancies concerning the source of the methamphetamine contamination in relation to "Use of premises" and associated charges under Section 12 of the Misuse of Drugs Act (New Zealand) 1975. Regardless, the final New Zealand standard, released in June 2017, set a single decontamination level for 'high-use areas' of 1.5 μg/100 cm 2 and a less stringent decontamination level for 'limited-use areas' of 3.8 μg/100 cm 2, with no requirement to determine the origin of the contamination.